2022
DOI: 10.1097/qai.0000000000003067
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Mortality After Loss to Follow-Up—A Linkage Study of People Living With HIV in Thailand and Malaysia

Abstract: Background: Linkage studies have reported high rates of previously unascertained mortality among people living with HIV (PLHIV) who have been lost to follow-up (LTFU). We assessed survival outcomes among PLHIV who were LTFU in Thailand and Malaysia, through linkages to a national death registry or HIV database.Methods: Data linkages with the national death registry or national HIV database were conducted in 2020 on all PLHIV who met LTFU criteria while enrolled in care at participating HIV clinical sites. LTFU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Study limitations include well-known limitations of observational studies for causal attribution, along with possible underascertainment of deaths and transfers to other sites of care in routine HIV service delivery data [ 30 32 ]. As tracing studies have reported rates of undocumented (i.e., “silent”) transfer ranging from 4% to 54% among patients lost to follow-up [ 30 32 ], true LTC may be overestimated in our study, and deaths and transfers are likely underestimated [ 33 ]. Although WHO began recommending the decentralization of HIV care in LMICs in the mid- to late 2000s, well before the adoption of universal HIV treatment guidelines in these settings [ 34 36 ] and we used a conservative definition of LTC [ 37 ], it is possible that decentralization has accelerated with the rollout of universal treatment policies, resulting more undocumented transfers, particularly among patients at centralized or tertiary care sites who silently transfer to peripheral HIV care facilities [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 91%
“…Study limitations include well-known limitations of observational studies for causal attribution, along with possible underascertainment of deaths and transfers to other sites of care in routine HIV service delivery data [ 30 32 ]. As tracing studies have reported rates of undocumented (i.e., “silent”) transfer ranging from 4% to 54% among patients lost to follow-up [ 30 32 ], true LTC may be overestimated in our study, and deaths and transfers are likely underestimated [ 33 ]. Although WHO began recommending the decentralization of HIV care in LMICs in the mid- to late 2000s, well before the adoption of universal HIV treatment guidelines in these settings [ 34 36 ] and we used a conservative definition of LTC [ 37 ], it is possible that decentralization has accelerated with the rollout of universal treatment policies, resulting more undocumented transfers, particularly among patients at centralized or tertiary care sites who silently transfer to peripheral HIV care facilities [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 91%
“…[ 21 , 22 ] Additionally, LTFU could be an indicator of death. [ 23 , 24 ] It is possible that some of the ART-experienced clients previously initiated and reengaged in care may have been failing on treatment but continued to receive suboptimal non-suppressive treatment and hence had increased risk of mortality. A systematic review and meta-analysis from sub-Saharan Africa reported a mean delay between confirmation of treatment failure and switch of therapy of 530 days.…”
Section: Discussionmentioning
confidence: 99%